Voting and contributing when the group is watching - Henry, Emeric. and Sidois, Louis Charles (American Economic Journal Microeconomics)
Members of groups and organizations often have to decide on rules that regulate their contributions to common tasks. They typically differ in their propensity to contribute and often care about the image they project; in particular, they want to be perceived by other group members as being high contributors. In such environments we study the interaction between how members vote on rules and their subsequent contribution decisions. We show that making contributions visible affects the calculus of reputation and the voting decisions, and can be welfare decreasing as it makes some rules more likely to be rejected. - Reproduced
Keywords: Rent-seeking, Lobbying, Elections, Legislatures, and Voting Behavior